HUBUNGAN FAKTOR INDIVIDU, LINGKUNGAN DAN FAKTA SOSIAL DENGAN ENTERPRENEURSHIP MAHASISWA UIN SYARIF HIDAYATULLAH JAKARTA - Nurhasanah, Nurhasanah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2015)
According to Peggy A. Lambing and Charles R. Kuehl in his entrepreneurship books, there are three factors that influence the determination of the behavior of entrepreneurs: the individuals, the ethno cultural environment, the circumstance in society. 50 student entrepreneur found in UIN SyarifHidayatullah Jakarta with diverse types of businesses, that showed students UIN has the potential to create national independence through entrepreneurship. A tangible manifestation of this potential will be implications for the strengthening of the nation's economic fundamentals. In this context, the researchers wanted to see how the relationship of individual factors, environmental and social facts with their entrepreneurship. How big are the correlation coefficient and which factors are more dominant. From the research it was found that all factors had a significant relationship to student entrepreneurship UIN Jakarta and the individual factors dominate.